Chammah J. Kaunda (ed.), Genders, Sexualities, and Spiritualities in African Pentecostalism: “Your Body is a Temple of the Holy Spirit.” - Johnathan Jodamus (African Journal of Gender and Religion (AJGR))
Moral discourses pertaining to gender and sexuality in Africa are certainly shaped by various religious norms and cultural beliefs, and for more than a decade, Pentecostalism has emerged as a primary area of research focus on this subject.1 The particular book under review fits within the ever-expanding body of literature on the intersections between African Pentecostalism, gender, and sexuality. The introductory chapter by Chammah J. Kaunda and Sokfa F. John centres Pentecostal and Charismatic spirituality as the lifeblood that sustains “beliefs, attitudes, moralities and legalities surrounding sexualities in Africa today.”